Work and family: marriage, children, child gender and the work hours and earnings of West German men - Hyung-Jai Choi; Jutta M. Joesch; Shelly Lundberg (Institute for the Study of Labor (IZA), 2005)
We find a strong association between family status and labor market outcomes for recent cohorts of West German men in the German Socio-Economic Panel. Living with a partner and living with a child both have substantial positive effects on earnings and work hours. These effects persist in fixed effects models that control for correlation in time-invariant unobservables that affect both family and work outcomes. Child gender also matters - a first son increases fathers' work hours by 100 hours per year more than a first daughter. There is evidence of son preference in the probability that a German man is observed to be coresiding with a son or a daughter. Men are more likely to remain in the same household with a male child than a female child and girls are underrepresented in the raw data. Controlling for selective attrition in our labor supply model reveals that men who remain with female children are strongly positively selected (in terms of their work hours) relative to men who remain with male children.
Keywords: J22; J12; J13; J16; 330; child gender; fatherhood; labor supply; family